The role of complementary lymphadenectomy in patients with incidental endometrial cancer - Barquet-Muñoz, Salim Abraham; Martínez-Alpizar, Pamela; Ramirez, Andrea; Rico-Mejía, Pamela; Pérez-Montiel, Delia; Sepúlveda-Rivera, Cintia María; González-Ruiz, Jonathan; Mohar, Alejandro; Pérez-Plasencia, Carlos; Cantú-de-León, David; Prada, Diddier (Frontiers in Oncology, 2025)
BackgroundUp to 3.0% of women are diagnosed with endometrial cancer after hysterectomy for apparently benign conditions. There is controversy about the benefit of complementary lymphadenectomy in incidental endometrial cancer after hysterectomy.ObjectiveTo evaluate the role complementary lymphadenectomy during a second surgery in the prognosis of patients with endometrial carcinoma.Study designThis was a retrospective cohort study of patients who were diagnosed with endometrial carcinoma from 2005 to 2019. Two groups were evaluated: patients who underwent a second surgery involving pelvic and/or para-aortic lymphadenectomy and patients who did not undergo surgical lymph node evaluation. Logistic regression was used to identify the factors associated with whether or not a complementary lymphadenectomy was performed. The Kaplan–Meier method was used to generate survival curves, and the log-rank test was used for comparisons. Univariate and multivariate analyses were performed with the Cox test.ResultsTwo hundred and sixty patients were included. Among them, 120 (46.15%) underwent complementary lymphadenectomy, and 140 (53.83%) did not. The factors associated with performing complementary lymphadenectomy in a second surgical procedure were higher grade, nonendometrioid histology and deep myometrial involvement. The factors associated with adjuvant treatment were high-grade histology, deep myometrial involvement, cervical involvement and extensive lymphovascular permeation. Complementary lymphadenectomy was not associated with adjuvant treatment (OR 0.85 95% CI 0.35-2.02), overall survival (Hazard Ratio (HR) 0.40 95% CI 1.16-1.00) or disease-free survival (HR 0.77 95% CI 0.38-1.59).ConclusionsNo clear therapeutic or prognostic role was identified for complementary lymphadenectomy during a second surgery in patients with endometrial cancer. Although adjuvant therapy was more common in patients who underwent complementary lymphadenectomy, it was not independently associated with receiving adjuvant therapy. Individualizing treatment decisions remains important when considering a second surgical procedure.